Annotated list of ichthyofauna of inland and coastal waters of Sakhalin Island. 1. Families Petromyzontidae-Salmonidae - Dyldin, Yury V.; Orlov, Alexei M. (Journal of Ichthyology, 2021)
A complete annotated list of marine, brackish-water, and freshwater ichthyofauna of Sakhalin Island and the adjacent southern part of the Sea of Okhotsk is provided for the first time in the entire history of the study of the fish population. It is based on a critical analysis of the literature data for the last 200 years, collection materials, and the results of our own long-term studies. The list includes 600 species in 4 classes, 44 orders, 17 suborders, 129 families, 50 subfamilies, and 312 genera. It presents both English and Latin (scientific) names, information on the ranges in the World Ocean and distribution within Sakhalin waters, and data on the conservation status, commercial importance, and abundance. For a number of species, the list also provides information on collection specimens, confirming their presence within the studied water area. For all species, the current ranges and taxonomic status are specified according to the new data, if any. The so-called controversial taxa are discussed. The first part provides brief information about the history of the study of the Sakhalin ichthyofauna, the geographical and oceanological characteristics of the study area, as well as the first 118 species of the annotated list belonging to 79 genera, 42 families and 20 orders in 4 classes.